Micro and nanoparticle monitoring during drilling operations using continuous particle size distribution instruments. (23rd July 2007) - Rodriguez, Monica; Handy, Rodney G.; Jackson, Mark J.; Robinson, Grant M.
Recent toxicological studies on airborne particles generated during the drilling process suggest that these types of particle can cause severe health effects after inhalation exposure. Although, the toxicological mechanism for these effects has not been explained yet, exposure to these particles in various settings has become a concern in environmental and occupational hygiene research. A pilot study was performed with respect to biological nanoparticle emissions and particle identification during an animal bone drilling process. The study evaluates several characteristics of a commercial ventilation system to determine the effects of the ventilation system to estimate personal exposure in the breathing zone. To evaluate this preliminary sampling strategy in workplace settings and to explore the performance of sampling instruments, concentration and particle distributions variations were observed under different airflow conditions, using laser and condensation particle counters and smoke tubes.